Decision-making in relation to health and environment: Toward sustainability economics - Söderbaum, Peter (Frontiers in Sustainability, 2022)
The challenge of sustainable development suggests that economics is defined as "multidimensional management of resources in a democratic society". A sustainability economics is needed which differs from mainstream neoclassical theory and method. Individuals are understood as "political economic persons" and organizations as "political economic organizations" guided by an "ideological orientation" or "mission". Markets are interpreted in network terms and decision-making as a "matching" process. Positional analysis is advocated as approach to investments at the societal level for example in roads and energy systems. It is argued that the proposed conceptual framework adds to our dialogue about policies for sustainability. In a democracy, radical institutional change need to be considered in attempts to make development of our political economic system sustainable rather than unsustainable.